The Convergence Rate of the Third and the Fourth Moments - Yeleyko, Ya.I.; Yeleyko, Ya.I. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2017)
The perturbation ε of the random environment Ω is considered. There is proved that as ε → 0 the perturbed third and the perturbed fourth moments differ from the third and the fourth moments respectively very little. The convergence rate of the perturbed third and the perturbed fourth moments to the unperturbed ones is investigated.